Giant basal cell carcinoma of the scrotum: A case report and review of the literature. Issue 4 (11th October 2022) - Ogawa, Hiroki; Kitamura, Shinya; Seo, Takashi; Yoshimoto, Norihiro; Yanagi, Teruki; Ujiie, Hideyuki
Abstract: Basal cell carcinoma (BCC) is the most common skin cancer. However, BCC on the scrotum is very rare, with an incidence of 0.03%. Giant BCC, in which the tumour is larger than 5 cm, has also been reported as a rare variant. Here, we report a 71‐year‐old male with a giant BCC on the scrotum and review similar cases reported in English. None of the four cases of giant BCC on the scrotum, including the present case, showed lymph node or distant metastasis. Wide local excision was conducted in all cases, and no recurrence was reported. The role of human papilloma virus in scrotal BCC development remains unclear.